2022
DOI: 10.1108/jefas-01-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Financial fragility and financial stress during the COVID-19 crisis: evidence from Colombian households

Abstract: PurposeOur findings indicate that workers with more financial education were more prepared to face the negative effects on their finances from COVID. This ability reduces the probability of becoming financially fragile and experiencing financial stress.Design/methodology/approachThe authors applied a survey questionnaire to 856 Colombian adults and used principal component analysis to build an index for each factor. Then, the authors used a linear regression model with the indexes to test our hypotheses and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This aligns with the primary theoretical model that underpins this scale’s construction ( Tito-Bentancur et al, 2021 ). Moreover, the FSSSCC/ ESECPS reliability coefficient value was satisfactory ( Streiner, 2003 ) and acceptable ( Hill and Hill, 2012 ), in line with what has been reported by other studies ( Heo et al, 2020 ; Cardona-Montoya et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…This aligns with the primary theoretical model that underpins this scale’s construction ( Tito-Bentancur et al, 2021 ). Moreover, the FSSSCC/ ESECPS reliability coefficient value was satisfactory ( Streiner, 2003 ) and acceptable ( Hill and Hill, 2012 ), in line with what has been reported by other studies ( Heo et al, 2020 ; Cardona-Montoya et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…Chhatwani and Mishra (2021) found that financial preparedness had a negative correlation with financial fragility during the COVID-19 pandemic because financially prepared individuals were able to have more resilient financial planning (savings and debts) and were less likely to be influenced by cognitive biases. Cardona-Montoya et al (2022) found that individuals with more financial literacy are more prepared to face the negative effects on their finances, which reduces the probability of becoming financially fragile (i.e. to decrease their income).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second type focuses on exploring the outcomes associated with financial fragility, where financial fragility serves as a contextual background factor (Bialowolski et al ., 2021; Chhatwani and Mishra, 2021b; Preston, 2022; Yu et al ., 2022). The third type seeks to identify factors that are linked to financial fragility, encompassing both risk factors that may increase the likelihood of financial fragility and coping factors that can help reduce it (Ali et al ., 2020; Cardona-Montoya et al ., 2022; Clark et al ., 2021a, b; Lusardi et al ., 2021; West and Mottola, 2016). Incidents of financial fragility are prevalent in the United States and other countries.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A study using data from Pakistan reveals that education, employment status and the industry of employment of the household head are the main determinants of financial fragility (Ali et al ., 2020). Utilizing data from Colombia, researchers have demonstrated that workers with more financial education are better prepared to mitigate the negative effects on their finances, thereby reducing the probability of becoming financially fragile (Cardona-Montoya et al ., 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%